The P7 approach to the Olympic challenge: Sharing a practical framework for mission preparation and execution - Collins, D.; Cruickshank, A. (International Journal of Sport and Exercise Psychology, 2015)
The Olympic Games represent the biggest and third biggest sporting occasions in the world (Summer and Winter, respectively). As such, dealing with the various challenges and optimising performance at this event has been an important dual focus for team leaders, coaches, performers, and their supporting sport psychologists. In this paper, we share an organisational approach to planning and preparation that, in our experience, provides an effective set-up for athletes, coaches, and support teams alike. Specifically, this presented framework enables the focused tasking of support staff and resources to address both individual and specific challenges. To illuminate the route via which this approach delivers its impact, underpinning mechanisms, advantages, and other considerations are also presented.